2001 Annual Conference Proceedings
DOI: 10.18260/1-2--9201
|View full text |Cite
|
Sign up to set email alerts
|

An Engineering Linkage To K 12 Teachers

Abstract: Engineering faculty at Iowa State University have worked collaboratively with teacher education faculty since 1996 to offer an undergraduate course entitled Toying with Technology to elementary and secondary education majors1, 2. The development of this technology literacy course provided students with an appreciation for the technological innovations that surround them. Studies have shown that students form many of their overall career and educational attitudes as early as elementary school. Elementary (and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Two main reasons were behind this selection. First the selected respondents are already online users; and second previous empirical works have shown that online behavior was not significantly different from a sample (Thakur & Summey, 2007;Gallagher et al, 2001). The questionnaire was pre-tested to ensure readability and validity before distribution.…”
Section: Methodology Data Collectionmentioning
confidence: 99%
“…Two main reasons were behind this selection. First the selected respondents are already online users; and second previous empirical works have shown that online behavior was not significantly different from a sample (Thakur & Summey, 2007;Gallagher et al, 2001). The questionnaire was pre-tested to ensure readability and validity before distribution.…”
Section: Methodology Data Collectionmentioning
confidence: 99%
“…in elementary education must complete a course in engineering design methods that is taught by faculty from the college of engineering [15]. The University of South Florida offers a course in STEM issues for pre-service middle school math and science teachers that is co-taught by faculty from engineering and education and teachers in a local school district [16], while at Iowa State University, education and engineering faculty jointly teach a class for education majors called Toying with Technology [17], and Hofstra University offers a unique K-5 STEM Education major that includes 4 required engineering education courses that are taught by faculty from the college of engineering [18]. Although all of these programs are promising, the effectiveness of this model of engineering teacher training has not yet been systematically investigated.…”
Section: Background and Motivationmentioning
confidence: 99%